A COMPARATIVE CLINICAL STUDY TO EVALUATE THE EFFICACY OF GREEVABASTI WITH PRASARINI TAILA AND NASYA KARMA WITH PARINITAKERIKSHEERA TAILA AS PRADHANA KARMA IN GREEVASANDIGATAVATA W.S.R. TO CERVICAL SPONDYLOSIS (International Journal of Ayurveda and Pharma Research, 2020)
The digitalization of the world has influenced people to have access on all the things through technologies like use of computers, mobiles etc and excess use of this has caused various problems and one among them is usage of these gadgets in improper position which is the causative factor for Greeva Sandhigatavata and shows Sandhi Shoola, Sandhi Shotha, Vatapoorna Druti Sparsha and Prasarana Akunchana Vedana which can be correlated to Cervical Spondylosis which also shows similar symptoms like pain in the neck, stiffness, radiating pain and tenderness. So the study was carried on 10 patients, 5 patients in each group to evaluate the efficacy of Greevabasti with Prasarini Taila in Group A and Nasya Karma with Parinitakeriksheera Taila in Greeva Sandigatavata w.s.r. to cervical spondylosis as Pradhana karma after Poorava Karma of Snehana and Swedana in both the groups. The study revealed that Sandhishoola (joint pain) and Sandhishotha (joint Swelling) where highly significant statistically and Sandhisthabdhata was significant statistically in Group A, and in Group B Sandhi Sthabdhata shown highly significant results.